Pemberdayaan UMKM Desa Baruga Melalui Pendampingan Sertifikasi Halal Manejemen Usaha dan Pemasaran Digital Berbasis Pendekatan ABCD - Nurfadilla, Ingka Tiara; Alam, Aisyah Hidayah Utami; Andillah, Andillah; Saputri, Ardila; Ridwan, Hilal; Rukman, Irsad; Hairuddin, Hairuddin; Bustang, Sarma (Indo-MathEdu Intellectuals Journal, 2026)
The Community Service Learning (CSL) programme in Baruga Village, Malili Sub-district, East Luwu Regency, was conducted from 7 July to 22 August 2025, focusing on empowering MSMEs through strengthening business legality, improving management capacity, and digital promotion. This programme was motivated by the low ownership of Business Identification Numbers (NIB), halal certification, and managerial skills among MSME actors. The method used was Asset-Based Community Development (ABCD) through the stages of inculturation, discovery, design, define, and reflection. The results of the activities show that four SME products successfully obtained halal certification and three SMEs obtained NIBs, accompanied by an increase in business actors' understanding of financial literacy and business management. In addition, students compiled business management modules, SME profile books, and digital promotional content as efforts to support market expansion. Overall, this KKN activity contributed to improving business legality, the confidence of SME actors, and strengthening the capacity of village SMEs in a sustainable manner.